How individual interest influences situational interest and how both are related to knowledge acquisition: a microanalytical investigation - Rotgans, Jerome Ingmar (2018)
The extent to which a student experiences situational interest during a learning task is dependent on at least two factors: (1) external stimuli in the learning environment that arouse interest and (2) internal dispositions, such as individual interest. The objective of the present study was to disentangle how both factors influence situational interest during task engagement. Two data sets were collected from primary school science (N = 186) and secondary school history students (N = 71). Path analysis was used to examine the influence of individual interest on seven situational interest measurements and knowledge acquisition. The results suggest that individual interest has only a significant influence on situational interest at the beginning of a task and then its influence fades. In addition, individual interest is not a significant predictor of learning. Only situational interest predicts knowledge acquisition. Implications of these findings for interest research are discussed.